2019
DOI: 10.1016/j.drudis.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Success factors of crowdfunding campaigns in medical research: perceptions and reality

Abstract: Crowdfunding in medical research is becoming more popular due to the shrinking and increasingly competitive government funding. In order to inform researchers applying for this complementary source of research funding, we investigate the determinants of successful crowdfunding campaigns in medical research. We find that establishing and maintaining professional contacts through social media is of major importance for successful crowdfunding campaigns; an additional tweet or retweet significantly increases the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 41 publications
6
74
0
Order By: Relevance
“…Additionally, Borst et al (2018), found a positive effect of project updates and tweets on the success of crowdfunding campaigns. This was in line with Aleksina et al (2019) findings which revealed that founders should establish and maintain professional contacts through regular updates to increase the probability of campaign success. Regular updates also create a sense of trust from the backers.…”
Section: Literature Reviewsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, Borst et al (2018), found a positive effect of project updates and tweets on the success of crowdfunding campaigns. This was in line with Aleksina et al (2019) findings which revealed that founders should establish and maintain professional contacts through regular updates to increase the probability of campaign success. Regular updates also create a sense of trust from the backers.…”
Section: Literature Reviewsupporting
confidence: 88%
“…Additionally, Song et al (2019) study recommended that crowdfunded campaigns with shorter funding days attract more backers. However, crowdfunded campaigns should not set very high or unrealistic goals as this may discourage potential backers (Aleksina et al, 2019). This argument was supported by Song et al (2019) who argued that project founders should set realistic funding goals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ultimately, we received 138% of the target (CHF 69,109) from 235 donors. This success is somewhat contradictory to the experiences reported in the scientific literature suggesting that crowdfunding can hardly yield sums larger than US $10,000 [4,10,11] and that similar to traditional funding agencies, donors are hesitant about supporting innovative projects [19]. What are the specific aspects of our campaign that could have contributed to its success?…”
Section: Principal Resultsmentioning
confidence: 59%
“…Lastly, SM can be directly used by health researchers to support prevention interventions to raise awareness and engage populations [ 78 ] and to crowdfund by promoting their research on SM. Indeed, crowdfunding can be eased by establishing professional contacts through SM and sharing campaigns [ 79 ].…”
Section: Discussionmentioning
confidence: 99%